The Influence of Locus of Control and Academic Stress on Academic Procrastination of Class XI Students at SMK Negeri 50 Jakarta - Afifah Tuzzakiyah; Roni Faslah; Corry Yohana (LAFADZ JAYA Publisher, 2023)
This study aims to determine the effect of locus of control and academic stress on academic procrastination in class XI students at SMK Negeri 50 Jakarta. The population in this study amounted to 244 respondents, and the sample was taken using a probability sampling technique, namely proportional random sampling with a total sample of 142 respondents. Validity test using product moment and reliability test using Cronbach's alpha. The data analysis technique used was a requirements test, classical assumption test, multiple linear regression test, and hypothesis testing with IBM SPSS version 23.0. The results of this study indicate that (1) there is a negative and significant influence of locus of control on academic procrastination of class XI students at SMK Negeri 50 Jakarta.